Critical theory and curriculum practice in STS education - Waks, Leonard J. (Journal of business ethics, 1989)
The STS education movement is identified and related to the critique of technology of the 1960s–1970s. The critics of technology included the system of education in their critiques. There is a practical tension or “contradiction” in attempting to develop their insights within the curriculum routines of the schools and colleges. This tension is explored under six categories: reductive knowledge, socialization of technical modes of thinking, technicalized processes of learning, the loss of meaning, radical monopoly over learning, and the socialization of secular values.